(untitled) (Archives of Pediatrics of Uruguay, 2022)
Since 2007, palliative care (PC) has been a part of the health benefits that all Uruguayan citizens are entitled to receive and, since then, accessibility has increased significantly. Objective: to describe the present development of pediatric palliative care services (PPC) in Uruguay and the patients assisted by health providers since the beginning of their services until 12/31/2020 and the key strengths and challenges perceived by these palliative care teams. Methodology: a consultation was carried out through a self-administered online survey and sent to the PPC service coordinators in Uruguay. Results: 19 teams were confirmed in 9/19 departments, 5/19 are integrated by professionals from the four recommended basic disciplines, the rest by different combinations of disciplines, with highly variable workloads. They provide assistance in: hospitalization 19/19, clinics 18/19, coordinated home care 13/19 and telephone assistance 10/19. 2957 children were assisted, 23% of them died. 16/19 teams report shared values and interdisciplinary teamwork as their main strengths, and 15/19 report human resource shortage as their main challenge. Conclusions: significant inequality persist regarding access to PPCs. We confirmed a high variability in teams’ integration and professional workload. It is necessary for the health authorities to continue to promote and demand the development of PPC teams in the institutions and departments that do not yet have them and the compliance with minimum quality standards in those that already operate